Salivary biomarkers for the prognosis of oncological and infectious diseases: a systematic review - Arbildo-Vega, Heber Isac; Panda, Saurav; Cruzado-Oliva, Fredy Hugo; Vásquez-Rodrigo, Hernán; Aguirre-Ipenza, Rubén; Meza-Málaga, Joan Manuel; Luján-Valencia, Sara Antonieta; Luján-Urviola, Eduardo; Farje-Gallardo, Carlos Alberto; Castillo-Cornock, Tania Belú; Serquen-Olano, Katherine; Padilla-Cáceres, Tania; et al. (Frontiers in Dental Medicine, 2025)
ObjectiveTo determine the salivary biomarkers that are used in the prognosis of oncological and infectious diseases.Materials and methodsA bibliographic search was carried out until July 2025, in the biomedical databases: PubMed, Cochrane Library, Scopus, EMBASE, Web of Science (WoS), Scielo, Science Direct and Google Scholar. Studies that were clinical trials, which reported the use of salivary biomarkers for the prognosis of oncological and infectious diseases, without time and language limits, were included. The Cochrane Handbook of Systematic Reviews of Interventions was used to assess the risk of bias of the included studies.ResultsThe preliminary search yielded a total of 189 articles, discarding those that did not meet the selection criteria, leaving only 16 articles for qualitative synthesis. These studies reported that the most widely used salivary biomarkers in the prognosis of oncological and infectious diseases are cortisol and interleukins.ConclusionsSalivary biomarkers, especially cortisol and key interleukins, demonstrate potential as non-invasive tools for the prognostic assessment and monitoring of oncological and infectious diseases. Further standardization and clinical validation are needed to support their integration into routine practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42021260764, PROSPERO CRD42021260764.